2017
DOI: 10.1155/2017/4312943
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Radial Clearance of a Squeeze Film Damper on the Vibratory Behavior of a Single Spool Gas Turbine Designed for Unmanned Aerial Vehicle Applications

Abstract: This study presents a numerical investigation using the finite element method on the vibratory behavior of a single spool gas turbine designed for unmanned aerial vehicle applications. The shaft of the rotor-bearing system is supported on a front bearing composed of a deep groove ball bearing with a vibration absorber element and a rear squeeze film damper bearing. Three radial clearances for the squeeze film damper were analyzed to determine the best geometric configuration for the rear bearing, considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Acknowledgments: All authors thank the support received and acknowledged in [1][2][3]. The first author would also like to thank CAPES and CNPq 385582/2006-4 for their financial support.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledgments: All authors thank the support received and acknowledged in [1][2][3]. The first author would also like to thank CAPES and CNPq 385582/2006-4 for their financial support.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In turbine discs, the use of Inconel alloys is a choice in the great turbine studied in this work has already been designed and is under development. With an approximate weight of 650 N, a maximum diameter of 0.350 m, and a maximum length of 1.50 m, that aeronautical gas turbine is capable of producing 5 kN of thrust at the rotational speed of 28,150 rpm [1][2][3][4]. Figure 1a,b illustrate the aeronautical gas turbine studied in this work on the test rig.…”
Section: Introductionmentioning
confidence: 99%
“…The generated mesh should be able to provide sufficiently accurate results according to the complexity of the geometry and physical phenomena involved. Several complex applications can be analyzed with sufficient accuracy level [4,5]. In computational numerical simulations, the pre-processing phase is one of the "bottle-neck" with respect to the computer processing time.…”
Section: Introductionmentioning
confidence: 99%
“…Mostafa and Abdolreza Ohadi Irannejad investigated the dynamic characteristic of a rotor supported on a novel SFD: MHSFD, and Mostafa Irannejad concluded that the rotor could avoid to be destroyed by controlling the electric current [15]. Geraldo Creci and Jose Orlando Balastrero did a research to obtain the optimum SFD clearance by analyzing the transient response of the rotor-SFD system [16]. Jaroslav Zapom�el investigated the vibration attenuation characteristics of MHSFD by constructing a novel model of MHSFD based on the bilinear oil presentation [17].…”
Section: Introductionmentioning
confidence: 99%